Literature Review : Evaluasi Program Projek Penguatan Profil Pelajar Pancasila (P5) Dengan Model CIPP untuk Meningkatkan Karakter Peserta Didik - Lufita, Inda Mey; Kanlatl Amalia; Erny Roesminingsih; Amrozi Khamidi; Mochamad Nursalim (Journal Of Administration and Educational Management (ALIGNMENT), 2025)
This research alms to analyze the evaluatlon of the lmplementation of Pancasila Student Profile Strengthening Project (P5) using CLPP model’s, wlth a focus on improving the character of students. The type of research used is Literature Review or library study. Data was collected through journals taken from Google Scholar, while data analysis was cariled out using a Systematic Literature Review (SLR) approach. Evaluatlon carried out using the CIPP model include evaluation of context, lnput, process and product. Thls evaluation process is very important to gather valuable informatlon regarding successes and challenges in implementlng the P5 program, as well as to provlde recommendatlons for future lmprovements.  Keywords: Literature Review, Evaluation, CIPP Model, Pancasila Student Profile